Penggunaan Mikroorganisme Lokal dari Berbagai Formula terhadap Kualitas Biourine Kambing Terfortifikasi - K. Mahmuda; Salundik; P. D. M. H. Karti (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2020)
Biourine which is widely known as liquid organic fertilizer is one of the alternative efforts in waste treatment, especially animal urine to become something that is more beneficial for the environment. One of the biourine benefit is to maintain soil fertility which is can increase farmer productivity. The aim of the research was to test the quality of local microorganisms (MOL) and goat biourine which had been made in different formulas, and to determine the best biourine in kale. MOL was made by four main raw materials, they are cow’s rumen, golden snail, bamboo shoots, and banana weevil. The making of MOL needed 14 days of processing in aerobic system. Then, 10% of MOL that had been made was added to goat urine to make biourine in the same aerobic system. The best biourine will be tested by watering kale. From the observations, it was obtained that the composition of raw materials from existing formulas affects the quality of the MOL produced. The quality affects the final result of the biourine. The best selected biourine has N and P content of 2.23% and 0.11% respectively. The amount of biourine applied to water kale was 0.4 ml / planting hole. The result showed kale which was watered by biourine treatment produced higher production levels than negative control plants but the difference was not significant. But these results was still lower than positive control by the treatment of chemical fertilizers.